2023
DOI: 10.3390/medicina59061146
|View full text |Cite
|
Sign up to set email alerts
|

rSO2 Measurement Using NIRS for Lower-Limb Blood Flow Monitoring and Estimation of Safe Balloon Occlusion/Deflation Time in Patients with PAS Who Underwent PBOA during CS

Abstract: We examined the utility of regional oxygen saturation (rSO2) measurement using near-infrared spectroscopy (NIRS) for monitoring lower-limb blood flow and estimate the safe balloon occlusion/deflation time in patients with PAS who underwent prophylactic balloon occlusion of the abdominal artery (PBOA) during cesarean section (CS). During CS, the NIRS probes were positioned on either of the anterior tibial muscles. rSO2 was measured continuously during balloon occlusion/deflation. A cycle consisted of inflating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Over the past 10 years, there have been 67 papers published in PubMed regarding the use of NIRS for brain perfusion monitoring during carotid endarterectomies (CEA), which implies that, due to its simplicity, NIRS is being widely adopted in this clinical setting [29,30]. Recently published clinical trials have reported the utilization of NIRS for peripheral tissue oxygen saturation monitoring in PAD patients [31][32][33]. Also, in 2022, Baltrunas et al discussed the use of NIRS in the context of PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 10 years, there have been 67 papers published in PubMed regarding the use of NIRS for brain perfusion monitoring during carotid endarterectomies (CEA), which implies that, due to its simplicity, NIRS is being widely adopted in this clinical setting [29,30]. Recently published clinical trials have reported the utilization of NIRS for peripheral tissue oxygen saturation monitoring in PAD patients [31][32][33]. Also, in 2022, Baltrunas et al discussed the use of NIRS in the context of PAD.…”
Section: Discussionmentioning
confidence: 99%
“…The final study group consisted of 70 healthy volunteers, of which 30 were a young group of volunteers with a median age of 23 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) years and 40 were an older group of volunteers with a median age of 70 (60-79) years. Analysis of body composition parameters showed significantly higher median values of body mass index (BMI), percentage of body fat (%PBF) and fat mass (FM) (p = 0.01) in the older group compared to the younger group.…”
Section: Characteristics Of the Study Groupmentioning
confidence: 99%
“…There is also a constantly growing interest among researchers in the possibility of using NIRS in monitoring changes in muscle oxygenation and blood flow during physiological and pathological conditions, e.g., during submaximal and maximum exercise [13,[20][21][22], to identify peripheral vascular disease [23], in chronic obstructive pulmonary disease (COPD) [24], in cardiovascular diseases [25] and in sepsis [26]. It has been found that during work the degree of deoxidation of skeletal muscles varies depending on the type of muscle, type of exercise and blood flow specific to a given area and health status [27,28]. Only a few authors refer to the use of NIRS in physiotherapy as a method for assessing the impact of physical or kinesiotherapy treatment or entire rehabilitation programs in therapeutic rehabilitation [3,29,30].…”
Section: Introductionmentioning
confidence: 99%